<The> specification of changes of the perception of wealth, poverty and happiness at the beginning of 21st century and identification of the economic and extra economic interactions theoretical and empirical approach - Rozborilová, Dária
Ekonomická a sociálna stratifikácia. Bohatstvo, chudoba a šťastie. Zmeny vo vnímaní bohatstva, chudoby a šťastia. Indikátory ekonomickej výkonnosti, konkurencieschopnosti a prosperity. Problém, dimenzie chudoby.